„Błogosławione pieśni malinowe. Fragmenty Norwidowskie” op. 43 Henryka Mikołaja Góreckiego – inspiracje, konteksty, determinanty stylistyczne - Miklaszewska , Joanna (Studia Chopinowskie, 2023)
Henryk Mikołaj Górecki’s Blessed Raspberry Songs. Norwid Fragments, Op. 43: inspirations, contexts and stylistic determinants Norwid’s inspirations in the works of Henryk Mikołaj Górecki were expressed in the 1980 cycle of Blessed Raspberry Songs. Norwid fragments for voice and piano op. 43. The aim of the article is to analyze the textual and musical layer of the work and to show the meaning of these songs against the background of Polish music at the turn of the 70s and 80s of the twentieth century. The cycle Blessed Raspberry Songs consists of four songs: 1. Blessed raspberry songs, 2. Each morning, when the shadows recede, 3. Compassion, 4. Oh! God …. Three songs have a two-part AB form, while the first song has a segmental structure with elements of the rondo form. The texts of the individual songs of the cycle are usually short excerpts from various works by Cyprian Kamil Norwid. Sacred connotations are visible both in the text and in the musical layer of Blessed Raspberry Songs. The melody and rhythm of the individual songs of the cycle contain allusions and reminiscences of Polish church songs. In the rhythmic and melodic layers of the song Compassion, one can also find reminiscences of the Polish national song Hej strzelcy wraz sung during the January Uprising. In all four songs of the cycle op. 43 there is a reduction of the rhythmic layer, visible especially in the vocal part. The melody of the vocal part, dominated by second intervals, is also limited. In the song cycle Blessed Raspberry Songs, three sources of inspiration are noticeable: songs by Karol Szymanowski and Mieczysław Karłowicz and, above all, Polish national song. The turn of the 1970s and 1980s was a period of social and political changes in Poland and events of great importance for Poles (the election of the Polish Pope, the rise of the resistance movement, the establishment of the Independent Self-Governing Trade Union “Solidarity”), which echoed in the works of Polish composers. A number of works composed by Henryk Mikołaj Górecki also belong to the trend of politically engaged music. They include, among others the Psalm Beatus vir dedicated to Pope John Paul II and Miserere, a work written in response to the Bydgoszcz events in March 1981. In 1980, Norwid’s text about the loss of spirit by the Polish nation under partitions, used in the song Compassion, gained a new, contemporary context, consisting in the introduction of an allusion to the times of the communist regime ruling in Poland. In Henryk Mikołaj Górecki’s Blessed Raspberry Songs the characteristics of the composer’s individual musical style are visible (using such tempos as Lento and Largo, dynamic contrasts). The limitation of the rhythm in combination with the sparing motives indicates the use of technical procedures of minimalistic provenance. The combination of minimalist procedures with elements of musical tradition places Górecki’s work within the framework of works representing postminimalism in European music.